Using structural equation model to estimate nitrate pollution in the Melen Watershed of the Turkey - Muhammed Ernur Akıner (Journal of Engineering & Processing Management, 2019)
In this study, Bayesian technique was applied in order toestimate export coefficients for the Melen Watershed.Furthermore, instead of calculating the contributions ofsubwatersheds individually, the whole watershed was consideredfor the estimation of the total load at the outlet of the MelenWatershed using the calculated nitrate export coefficient. TheBayesian approach has the goal of combining prior knowledgewith data to optimally use both sources of information. Success ofthe Bayesian approach is directly proportional to sufficiency ofdata for acquiring the prior information about estimands.Bayesian analysis was conducted through Structural EquationModel (SEM) using AMOS software and posterior informationabout land use based export coefficients was obtained throughMarkov Chain Monte Carlo (MCMC) method. Estimated land usebased nitrate export coefficients are in kg/km2/day unit. Inaddition, monthly river retention value of nitrogen in allsubwatersheds of the Melen Watershed were estimated. Thisinformation was used in order to predict nitrate exportcoefficients appropriately. This study is aimed to be an importantprecedent for other basins that are determined as in priority interms of pollution by The Ministry of Forest and Water Works ofTurkey.
Keywords: AMOS; Bayesian approach; Melen Watershed; MCMC; nitrate export coefficient; Structural Equation Model